The effects of urbanization on China's forest loss from 2000 to 2012: Evidence from a panel analysis. (20th March 2019) - Lin, Yuying; Qiu, Rongzu; Yao, Jixue; Hu, Xisheng; Lin, Jinguo
Abstract: Forest loss has severe impacts on global environment change and biodiversity. However, few studies have used panel models to analyze forest loss at the national level, attributed to the limited time-space-series data on the forest loss at such large scale. The freely accessible Landsat images provide data to derive the global forest loss at a high spatial resolution of 30 m (Hansen et al., 2013), which make it possible to carry out this study. Here we used the global forest loss dataset as a data source, a space-time panel model for 31 provinces, autonomous regions, or municipalities in mainland of China from 2000 to 2012 were built to investigate the relationship between the urbanization process and the forest loss both at the national and regional level. The results indicated that (1) the forest loss area of each province were between 3 and 89 ha to more than 89 ha during 2001 and 2012, with larger area of forest loss in the southern and north-eastern regions, while less forest loss in the central and western region. (2) In the study period, the forest loss rates were more than 4% in the southern China, while the rates were less than 0.1% in most of the northwest China; and the annual forest loss demonstrated an aggravated trend in most provinces of China. (3) There exists a scale effect and regional divergence in the impact of urbanization on forest loss: urbanization level is among the most critical factor affecting forest loss at the national level; while at the regional level, the most sensitive factor for forest loss is road mileage in the eastern region, urban green area in the central region, while urban level in the western region. This study may help to advance the understanding of the impact of urbanization process on China's forest loss, and therefore it provides good policy implications to make more effective and comprehensive solutions to reduce the loss of forests.